On Some Fixed Point Results for Cyclic \((α,β)\)-admissible Almost z-Contraction in Metric-Like Space with Simulation Function - Mishra, Snehlata; Dubey, Anil Kumar; Mishra, Urmila; Dubey, R. P. (Communications in Mathematics and Applications, 2022)
In this paper, we present some fixed point results in the setting of metric-like space by defining a cyclic \((α,β)\)-admissible almost z-contraction embedded in simulation function. Suitable examples are also established to verify the validity of the results obtained.